Study of Fatalities due to Lightning in Nagpur Region of Maharashtra - Shrigiriwar, Manish B; Gadhari, Ramesh K; Jadhao, Vijay T; Tingne, Chaitanya V; Kumar , Narendra B (Journal of Indian Academy of Forensic Medicine, 2014)
In Nagpur region of Maharashtra (India), many deaths were reported due to lightning strikes. In most cases of deaths due to lightning, bodies of deceased persons were found in remote areas with torn clothes and burn injuries. The injuries present over body may apprehend the relatives and raise suspicion of foul play. In this study total 31 cases were studied which were brought for medico legal post-mortem with history of lightning of which 87% were farmers and farm labourers. Twenty nine percent of cases belonged to the age group of 41-50 years. Most of the cases were found in the months of June, July and October. Filigree burns were found only in 4 cases. Careful examination of victims along with history of thunderstorm in the vicinity will help the autopsy surgeon to confirm the diagnosis of lightning.